Overview of the Tuberculosis (TB) Case Overview of the Tuberculosis (TB) Case Management Program Management Program in Baubau City in 2024 - Taswin, Taswin; Fahrin Amrullah, Muhammad; Fitriani, Fitriani; Wahyuddin, Wahyuddin; Dahmar, Dahmar; Endriana Amiruddin, Eky (Dian Nuswantoro Semarang, 2025)
Based on data from the Baubau City Health Service, in 2021 there were 334 cases and in 2022 there were 532 cases. The Case Notification Rate (CNR) for all TB cases in Baubau City is 138 per 100,000 population. This shows that among 100,000 residents there were 138 new patients found. The aim of the research is to find out an overview of the implementation of the Tuberculosis Case Management Program in Baubau City. The type of research used is quantitative with a descriptive approach. The entire population used as a sample was 35 people. The sampling technique uses total sampling. The research was conducted in May-June 2024. Data analysis was carried out univariately using SPSS. The research results showed that the human resource variable was sufficient for 30 respondents (85.7%) and less for 5 respondents (14.3%). The variable of adequate drug availability was 22 respondents (62.9%) and 13 respondents (37.1%) were lacking. The variables of sufficient facilities and infrastructure were 27 respondents (77.1%) and 8 respondents (22.9%) were lacking. The conclusion in this research is that Human Resources in the program for handling TB cases are quite good, namely 85.7%, Availability of Medicines is quite good, namely 62.9%, and Facilities and Infrastructure in the program for handling TB cases are quite good, namely 77.1%.